Examining the Relationship between Accruals and Financing using Equity Issuance and Debt Instruments Case Study: Listed Companies on Tehran Stock Exchange - elham poya (راهبرد مدیریت مالی, 2014)
Abstract The purpose of this study is to compare the financial performance of the companies with their accruals and financing. The model of the research has been formed using total accruals, discretionary accruals and financing support as the independent variables, and future stock returns as the dependent variable. The methodology of the present research is practical regarding the purpose and has been conducted using correlation method. The data collection has been conducted using desk study. The population of this study includes the companies listed on Tehran Stock Exchange among which, due to the limitations of the study, 46 companies have been selected. Data needed to test this hypothesis has been collected by two software programs, i.e. RAHAVARD NOVIN and TADBIR PARDAZ from the company's financial statements during 2004-2011. Data analysis was performed using EVIEWS software, Ver. 6. The results of the study indicate that there exists no correlation between the total accruals and discretionary accruals represented by the earnings management with stock returns. External debts and equity were two variables considered for external financing. There is no significant relationship between efficiency and equity stock futures, however, there exists a negative correlation exists between debt and future stock returns.